MAPPING THE MAIN CHARACTERISTICS OF EXCELLENT TEACHERS: A PHENOMENOLOGICAL STUDY - Miruna Luana MIULESCU; Antoaneta-Firuţa TACEA (National Centre for Policy and Evaluation in Education, 2022)
Teaching is a crucial component of any sensible approach to ensuring quality education. However, there is no adequate, integrated perspective on the core qualities that make for excellence in teaching. Our study seeks to discover people who are examples of excellence in teaching in order to determine a set of excellence-associated characteristics. The participants of the present study were primary school teachers (n=11) from Romania. By making use of a qualitative inquiry, data was collected through semi-structured interviews and observations of school lessons. The key findings suggest that there is no single template for excellence in teaching. According to the data, there are three key aspects that can be attributed to excellent teaching: a passion for teaching, authentic relationships with students, and critical reflection. Recommendations for sustaining high-quality teaching are discussed.